Hubungan Pengetahuan dan Sikap terhadap Pengelolaan Air Bersih di Desa Padaidi Kecamatan Sebatik Kabupaten Nunukan - Rosmalah Rosmalah; Firdaus Daud; Muhammad Danial (UNM Journal of Biological Education, 2023)
This study is an expost facto research that aims to examine whether there is a relationship between knowledge and attitude on clean water management in Padaidi Village of Sebatik subdistrict in Nunukan district. The independent variables in this study were knowledge and attitude, while the dependent variable was clean water management. The population of the study were all heads of families in Padaidi Village of Sebatik subdistrict in Nunukan district spread over 4 RTs, while the sample was 87 which were taken by incidental sampling technique. The data collection technique used a questionnaire. The data analysis technique employed descriptive analysis and inferential analysis. Based on the results of inferential data analysis, it is obtained that there is a positive and significant relationship between knowledge and clean water management which is in moderate category. Attitude has a positive and significant relationship with waste management at the level of strong relationship. There is a positive and significant relationship between knowledge and attitude on clean water management in moderate category. The biggest effective contribution to the dependent variable (clean water management) is given by knowledge with 50% and attitude with 46%. The total effective contribution is 96%, which means knowledge and attitude collectively make an effective contribution by 96% to clean water management in Padaidi Village of Sebatik subdistrict in Nunukan diistrict, while 4% is influenced by other factors not examined.